Retrospective study of severe acute malnourished children in nutrition rehabilitation center of Madhya Pradesh, India: Management and outcome - Bande, Bhushan Ashvinikumar; Thora, Sharad (Indian Journal of Child Health, 2019)
Introduction: Nutrition rehabilitation centers (NRCs) are established for optimal management of severe acute malnourished (SAM) children. Results of different NRCs vary in terms of outcome. Objective: The objective of the study was to know the morbidity and outcome pattern of SAM children. Materials and Methods: SAM children aged 0–59 months admitted during 2 years period in NRC of district hospital (secondary care center) of central India were enrolled in the study. Data of these children such as age, sex, weight on admission and discharge, complications, treatment, and outcome were studied. Results: A total of 993 children were admitted during 2 years April 2016–March 2018. Male children were 530 (53.37%) and female were 463 (46.62%). 93 (11.17%) children had mid-upper arm circumference